Integrating Islamic Values with the Right to Be Forgotten: A Legal Approach to Addressing Deepfake Pornography in Indonesia - Ramadhani, Evyta Rosiyanti; Rachmawati, Ayudya Rizqi; Kurnikova, Roro Hera (De Jure: Jurnal Hukum dan Syari'ah, 2025)
The potential for deepfake pornography to infringe upon personal data protection and violate privacy and dignity has become a significant concern. This study examines the role of the Right to Be Forgotten (RTBF) as a legal mechanism to mitigate the harmful effects of deepfake pornography in Indonesia, utilising a normative legal research approach and analysing extant regulations, including the Personal Data Protection (PDP) Law and the Electronic Information and Transactions (IET) Law, as well as Islamic legal principles on the protection of human dignity. The findings of the study suggest that while Indonesia provides a legal basis for RTBF, its implementation is hindered by limitations in Article 15 of the PDP Law, which restricts data deletion requests. The study proposes amendments to this article to enhance victim protection and argues for integrating RTBF with Islamic values to reinforce the moral and ethical necessity of erasing non-consensual deepfake content. To ensure effective enforcement, it is essential to strengthen the legal frameworks, foster collaboration between technology companies and regulators, and enhance digital literacy. The study concludes that effective implementation of RTBF has the potential to serve as a critical safeguard against deepfake pornography, thereby ensuring individuals can regain control over their digital identities and privacy in an evolving technological landscape.